2013
DOI: 10.1016/j.carbpol.2013.04.095
|View full text |Cite
|
Sign up to set email alerts
|

The influence of amylose-LPC complex formation on the susceptibility of wheat starch to amylase

Abstract: a b s t r a c tThis study was aimed to assess the role of lysophosphatidylcholine (LPC) in the development of slowly digestible starch (SDS). The influence of LPC, on the enzymatic degradation of diluted 9% wheat starch suspensions (w/w) was investigated, using an in vitro digestion method. Wheat starch suspensions containing 0.5-5% LPC (based on starch) were heated in a Rapid Visco Analyser (RVA) till 95• C and subjected to enzyme hydrolysis by porcine pancreatic ␣-amylase at 37• C for several digestion perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…The core of the granules remains dark, inferring that the lipid‐dye molecules do not interact with the inner structures of the granules due to the protective coating generated by the lipid‐dye molecules already linked to the outer part of the starch granule, or that penetration is hindered by their bulky size and presence of the polar head. From this evidence, we concluded that in the case of un‐gelatinized potato starch granules lipid‐dye molecules at low concentration selectively complex with the outer amylose chains of the granules, as previously reported by our group as well as others .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The core of the granules remains dark, inferring that the lipid‐dye molecules do not interact with the inner structures of the granules due to the protective coating generated by the lipid‐dye molecules already linked to the outer part of the starch granule, or that penetration is hindered by their bulky size and presence of the polar head. From this evidence, we concluded that in the case of un‐gelatinized potato starch granules lipid‐dye molecules at low concentration selectively complex with the outer amylose chains of the granules, as previously reported by our group as well as others .…”
Section: Resultssupporting
confidence: 87%
“…Among others, the amylose‐lipid inclusion complex has been demonstrated to have an influence on the staling . Recently, the inclusion complex formation between amylose in native wheat starch and lysophosphatidylcholine (LPC) was reported, underlying the effects of such inclusion on the structural properties and the susceptibility to amylase of starch .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic complexing reagents (such as fatty acids) can remain within the helix through van der Waals forces between lipids and the adjacent carbon–hydrogen of amylose . Meanwhile, the quantity and stability of starch–lipid complexes might be determined by the starch category, amylose chain length, nature of the lipid, solvent, and processing conditions . Starch–lipid complexation might be better assessed by a joint experimental and molecular mechanics approach because amylose–vanillin complexation has been assessed by experimental and theoretical analysis and computational techniques have been employed to fundamentally understand the behavior of helically structured amylose in water/DMSO mixtures .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of amylose inclusion complexation with LPC on the functional properties and thermal transitions of wheat starch was previously reported. In addition, a lower susceptibility to α‐amylase digestion due to amylose–LPC complexation was proven. However, it is still unknown if the amylose–LPC complexes remain stable during enzyme hydrolysis, e.g., if the LPC chains remain inside the amylose helix.…”
Section: Introductionmentioning
confidence: 99%